2012
DOI: 10.1039/c2mt20091k
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxylamido–amino acid complexes of oxovanadium(v). Toxicological study in cell culture and in a zebrafish model

Abstract: Oxovanadium(V) complexes [VO(NH(2)O)(2)(val)] and [VO(NH(2)O)(2)(met)] caused inhibition of cell proliferation in two osteoblast cell lines, MC3T3-E1 and UMR106, as well as the viability of zebrafish eggs. In MC3T3-E1, both compounds inhibited cell proliferation (up to ca. 40% at 25 μM [VO(NH(2)O)(2)(val)] and 25% at 25 μM [VO(NH(2)O)(2)(met)]). This effect occurs in a dose response manner from 2.5 μM (p < 0.01) with a more deleterious action of [VO(NH(2)O)(2)(met)]. In UMR106 tumoral cells, [VO(NH(2)O)(2)(val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 76 publications
0
8
0
1
Order By: Relevance
“…62 In the past, we and other researchers have successfully used this model for studying in vivo toxicity of new prospective metal-based drugs. 63,64 Being [Pt(L3)(dppf)](PF 6 ) the most active and selective compound of the new series, its in vivo toxicity on zebrafish embryos was tested. All zebrafish embryos were alive in the [Pt(L3)(dppf)](PF 6 ) whole concentration range examined (1-100 M) and no apparent toxicity was observed at the endpoint (48 h) of the assays.…”
Section: In Vivo Toxicitymentioning
confidence: 99%
“…62 In the past, we and other researchers have successfully used this model for studying in vivo toxicity of new prospective metal-based drugs. 63,64 Being [Pt(L3)(dppf)](PF 6 ) the most active and selective compound of the new series, its in vivo toxicity on zebrafish embryos was tested. All zebrafish embryos were alive in the [Pt(L3)(dppf)](PF 6 ) whole concentration range examined (1-100 M) and no apparent toxicity was observed at the endpoint (48 h) of the assays.…”
Section: In Vivo Toxicitymentioning
confidence: 99%
“…Oxidative stress is one of the main factors reported that trigger the deleterious actions of metal-based compounds. 44,45 For a better understanding of the possible mechanism involved in the cytotoxicity of both complexes in cancer cell lines, we evaluated the effect of complexes 1 and 2 on oxidative stress through the oxidation of the probe DHR-123. DHR-123 is a mitochondria-associated probe that selectively reacts with hydrogen peroxide.…”
Section: Ros Productionmentioning
confidence: 99%
“…It has been reported that these compounds, depending on the cellular line, may promote the generation of the reactive oxygen species (ROS) mainly in the mitochondria (Leon et al 2012a, 2014b; Rivadeneira et al 2009; Di Virgilio et al 2011) leading to a decrease of glutathione (GSH) concentration. GSH is one of the mayor reducing agents responsible for maintaining the cellular redox status through the balance of the couple glutathione/glutathione disulphide (GSH/GSSG).…”
Section: Resultsmentioning
confidence: 99%